THE RUBOI OF NAJMIDDIN KUBRO AND BAHAUDDIN NAQSHBAND ABOUT THE WORLD: A PHILOSOPHICAL ANALYSIS (TAMADDUN NURI JURNALI, 2024)
The article provides a philosophical analysis of Najmiddin Kubro, the founder of the Kubrawian doctrine in Tasawwuf, and Bahuddin Naqshband, the founder of the Naqshbandi doctrine, their views on the world described in two rubies. There is and is not a mortal, an immortal based on their thoughts.